2011
DOI: 10.1007/s11207-011-9842-2
|View full text |Cite
|
Sign up to set email alerts
|

Design and Ground Calibration of the Helioseismic and Magnetic Imager (HMI) Instrument on the Solar Dynamics Observatory (SDO)

Abstract: The Helioseismic and Magnetic Imager (HMI) investigation (Solar Phys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
763
2
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,744 publications
(773 citation statements)
references
References 9 publications
5
763
2
3
Order By: Relevance
“…The HMI instrument design and planned processing scheme are described by Schou et al (2012b) and Scherrer et al (2012). The SDO mission, launched 11 February 2010, is described by Pesnell, Thompson, and Chamberlin (2012).…”
Section: The Hmi Instrument and Data Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…The HMI instrument design and planned processing scheme are described by Schou et al (2012b) and Scherrer et al (2012). The SDO mission, launched 11 February 2010, is described by Pesnell, Thompson, and Chamberlin (2012).…”
Section: The Hmi Instrument and Data Flowmentioning
confidence: 99%
“…To perform this conversion the polarimetric model described in Schou et al (2012b) is used, including the corrections that depend on the front window temperature and the polarization selector temperature. At each point in the image a least-squares fit is then performed to derive I Q U V from the six observed polarization states.…”
Section: Stokes Vector Processing Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1(a) shows the G-band image of the region taken with Hinode/SOT. Contours in Figure 1(b) indicate the line-of-sight magnetic fields observed with Helioseismic and Magnetic Imager (HMI; Schou et al, 2012) onboard the Solar Dynamic Observatory (SDO; Pesnell, Thompson, and Chamberlin, 2011) superposed on the continuum image from SDO/HMI. It can be seen that the preceding sunspot had a negative polarity and the following sunspot groups had a positive polarity.…”
Section: Observation and Analysismentioning
confidence: 99%
“…Because there is a possibility − even if the event has no WL enhancements from the SOT data − that WL emission may exist out of the SOT field of view, we also checked the continuum data from the Helioseismic and Magnetic Imager (HMI) [29,30] onboard the Solar Dynamics Observatory (SDO) [31]. We found that both events had WL emission observed simultaneously by both instruments.…”
Section: Event Selectionmentioning
confidence: 99%